The Ecosystem Approach in Ocean Planning and Governance Perspectives from Europe and Beyond - Langlet, David; Rayfuse, Rosemary (Publications on Ocean Development, 2018)
Applying much needed legal and social sciences perspectives, the book provides in depth analyses of lessons learned and remaining challenges associated with making the Ecosystem Approach fully relevant and operational in various fields of marine governance. Readership: The book is relevant to everyone interested in what the Ecosystem Approach may offer in relation to sustainably governing the oceans, including academics, civil servants, politicians and civil society representatives.